2013
DOI: 10.1111/mec.12272
|View full text |Cite
|
Sign up to set email alerts
|

Steep clines within a highly permeable genome across a hybrid zone between two subspecies of theEuropean rabbit

Abstract: Maintenance of genetic distinction in the face of gene flow is an important aspect of the speciation process. Here, we provide a detailed spatial and genetic characterization of a hybrid zone between two subspecies of the European rabbit. We examined patterns of allele frequency change for 22 markers located on the autosomes, X-chromosome, Y-chromosome, and mtDNA in 1078 individuals sampled across the hybrid zone. While some loci revealed extremely wide clines (w>=300 km) relative to an estimated dispersal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 77 publications
12
62
0
Order By: Relevance
“…same group. Geographical isolation was found for wild rabbits (Fuller et al, 1997;Carneiro et al, 2013;Alda and Doadrio, 2014). In this study, we confirmed the spatial representation of the genetic inter-individual distances using the FCA analysis (Figure 3).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…same group. Geographical isolation was found for wild rabbits (Fuller et al, 1997;Carneiro et al, 2013;Alda and Doadrio, 2014). In this study, we confirmed the spatial representation of the genetic inter-individual distances using the FCA analysis (Figure 3).…”
Section: Discussionsupporting
confidence: 71%
“…They reported a lower MNA and PVT (ranging from 3.65 to 3.94 and 1 to 8) than those observed in our study in Table 2. These variations might be due to a genetic bottleneck position in other Egyptian local rabbit breeds (Emam et al, 2016). Positive values F IS.…”
Section: Discussionmentioning
confidence: 99%
“…This dataset was obtained in rabbits sampled at some distance from the primary contact zone (Figure S1), but in geographic regions that nonetheless show high levels of introgression [21], [24][27] (see Figure S2). …”
Section: Resultsmentioning
confidence: 99%
“…, ; Carneiro et al . , ). Cruickshank & Hahn () provide several explanations for the apparent inconsistency.…”
Section: Heterogeneous Gene Flow Vs Heterogeneous Selectionmentioning
confidence: 99%